The impact of physical activity on subjective wellbeing in college students: the chain-mediating role of rumination and mindfulness - Wang, Shimeng; Lu, Bochun; Zhang, Xinming (Frontiers in Psychology, 2025)
BackgroundSubjective wellbeing (SWB) is an important indicator of mental health, and physical activity (PA) has been shown to have a positive impact on SWB. However, the specific pathways through which PA enhances SWB via psychological mechanisms remain unclear. Cognitive regulation theory suggests that emotional experiences are influenced by cognitive processes, where rumination (RT) and mindfulness (MDS) play key roles in regulating emotional states. This study aims to explore the chain-mediating roles of RT and MDS in the relationship between PA and SWB, in order to deepen the understanding of how PA affects mental health.MethodsThis study used a cross-sectional design and collected data on PA, RT, MDS, and SWB from university students through a questionnaire survey. A total of 1,075 college students (Mage = 19.84, SD = 1.36; 48.9% male) from China participated in the study. Pearson correlation analysis was used to explore the relationships between variables, and PROCESS Model 6 was employed for mediation analysis to examine the chain-mediated effects of PA on SWB through RT and MDS.ResultsThe results indicate that PA has a significant direct effect on SWB, and it also influences SWB indirectly through RT and MDS. Specifically, PA reduces RT, and the decrease in RT further enhances MDS. Additionally, PA directly promotes MDS, and higher levels of MDS contribute to higher SWB. These findings suggest that the positive impact of PA on SWB is not only due to emotional regulation but also involves the optimization of cognitive processes, including reducing negative thinking and enhancing positive psychological resources.ConclusionThis study reveals the chain-mediated mechanism through which PA enhances SWB by reducing RT and increasing MDS. These findings highlight the importance of integrating exercise and cognitive regulation in mental health interventions. The study suggests that combining exercise training and MDS interventions may be a more effective strategy for promoting mental health. Future research should explore how different types of exercise affect MDS and optimize exercise-cognitive interventions for specific populations.